Efektivitas Penegakan Hukum Terhadap Pelaku Tindak Pidana Korupsi di Kabupaten Bone - Tahril, Tahril (CV. Social Politic Genius (SIGn), 2023)
This study aims to determine the law enforcement against corruption in Bone Regency, Sulawesi Province, and the factors that influence it. This type of research is empirical legal research with a quantitative descriptive in nature. This research was conducted within the Bone Police, Bone District Attorney, and Bone District Court. The data collection techniques used in this research were questionnaires, documentation, and literature study. The data analysis technique used is quantitative data analysis techniques. The results showed that law enforcement against perpetrators of corruption in Bone Regency is still not effective, this is because there are still several agencies that carry out investigations into criminal acts of corruption, such as police investigations, sometimes unable to prove their investigations. Factors that influence law enforcement against perpetrators of corruption in Bone Regency are factors of legal structure, factors of legal culture and factors of public legal awareness. Law enforcers are expected to submit corruption investigations to the Prosecutor's Office, because these institutions are very professional in handling corruption crimes.